2016
DOI: 10.1186/s12864-016-2667-5
|View full text |Cite
|
Sign up to set email alerts
|

The expansion of heterochromatin blocks in rye reflects the co-amplification of tandem repeats and adjacent transposable elements

Abstract: BackgroundA prominent and distinctive feature of the rye (Secale cereale) chromosomes is the presence of massive blocks of subtelomeric heterochromatin, the size of which is correlated with the copy number of tandem arrays. The rapidity with which these regions have formed over the period of speciation remains unexplained.ResultsUsing a BAC library created from the short arm telosome of rye chromosome 1R we uncovered numerous arrays of the pSc200 and pSc250 tandem repeat families which are concentrated in subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 80 publications
3
32
0
Order By: Relevance
“…5, 4, 7) except of rye, where a minor difference was observed in replication dynamics of telomeric sequences. Telomeric regions of rye comprise large heterochromatic blocks (Appels et al , 1978; Evtushenko et al , 2016) and our results showed, that DNA loci closely connected to heterochromatic block (probably flanking regions) were replicated at late S phase, while telomeres located out of heterochromatin were replicated earlier, during middle S phase (Fig. 4B, D, E).…”
Section: Resultssupporting
confidence: 67%
“…5, 4, 7) except of rye, where a minor difference was observed in replication dynamics of telomeric sequences. Telomeric regions of rye comprise large heterochromatic blocks (Appels et al , 1978; Evtushenko et al , 2016) and our results showed, that DNA loci closely connected to heterochromatic block (probably flanking regions) were replicated at late S phase, while telomeres located out of heterochromatin were replicated earlier, during middle S phase (Fig. 4B, D, E).…”
Section: Resultssupporting
confidence: 67%
“…Telomeric CMA bands are most likely related to rDNA sites as seen in most plant species (Barros e Silva et al, 2010;Castro et al, 2016;Marinho et al, 2018). Differences among species could be related tochromosome rearrangements and the amplification and reduction of rDNA sites caused by satellites or transposable sequences (Mehrotra and Goyal, 2014;Evtushenko et al, 2016;Saze, 2018).…”
Section: Heterochromatin Patternsmentioning
confidence: 98%
“…(2n = diploid chromosome number, FN = Fundamental Number, NOR = Nucleolus Organizer Region, ITS = Interstitial Telomeric Sequence, m = metacentric, sm = submetacentric, st = subtelocentric, a = acrocentric chromosomes p = short arm, q = long arm). 17; pericentromeric the dispersal of the 18S rDNA sequences in A. falcatus and A. microlepis may have been facilitated by their proximity to the telomere or by ectopic recombination in meiosis (Pedrosa-Harand et al 2006;Cazaux et al 2011;Evtushenko et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible type of arrangement is the translocation of major ribosomal 18S sites, which were present in four other sites, in addition to the NORs. This movement may have been facilitated by transposable elements (TEs) associated with the heterochromatin, which has great potential to cause chromosomal rearrangements, as well as through ectopic recombination that can generate intrachromosomal recombination between copies of the same family of transposable elements, arranged in opposite positions (Kidwell 2002;Grewal and Jia 2007;Skipper 2007;Raskina et al 2008;Delprat et al 2009;Cioffi et al 2010;Evtushenko et al 2016). The genomes of A. microlepis and A. prope microlepis differed also in terms of their ITSs, given not only that the ITSs were present in 19 chromosome pairs in one species, and in 18 pairs in the other one, but also the fact that these chromosomes were different, as well as the polymorphism between the homologs of pair 19 in A. prope microlepis.…”
Section: Groupsmentioning
confidence: 99%